A qualitative analysis of students' perceptions of videos to support learning in a psychomotor skills course. (19th June 2018) - Botelho, M. G.; Gao, X.; Jagannathan, N.
Abstract: Introduction: This qualitative study analysed students' experiences and perceptions about different types of videos in a psychomotor skills course, relating to clinical knowledge and skills and how they benefited learners in and out of the classroom. Methods: Subjects were recruited from 4th and 5th year dental undergraduate programme. The recruitment was terminated after 24 students participated since data saturation was reached. A semi‐structured interview was conducted with each participating student, digitally recorded and transcribed verbatim. A thematic analysis was performed using an inductive approach to identify key themes. Results: Four key domains were identified from thematic analysis: functionality and access; learning and understanding; clinical skills preparation and performance and supplementary learning resources. Students perceived videos to be an important and vital learning tool relating to its on‐demand access, control of functionality and use for particular needs that is not possible from textbooks or lectures. Video learning materials allows students to clarify knowledge, improve cognitive thinking and enhance revision of theoretical concepts and clinical skills. Two types of video were regarded as particularly useful as students reported being actively and cognitively engaged in the learning content and broadened their clinical experience. In addition, students reported mental preparation of clinical psychomotor skills using their own mental visualisation which enabled them to prepare for the clinical care of their patients. Conclusion: This qualitative research supports the benefits of learning from videos in relation to convenience of access and functionality of the videos. In addition, it shows novel aspects to learning from videos that are more cognitively engaging and in mental preparation of clinical skills prior to patient care.